El paradigma de Pigmalión en el poema 14 de Pablo Neruda - Martínez Sariego, Mónica María (Collectanea Philologica, 2024)
The article discusses the possible influence of Ovid on poem 14 of Veinte poemas de amor y una canción desesperada (1924) by Pablo Neruda, specifically through the paradigm of Pygmalion (Met. X, 243-297), which the Chilean poet uses to develop themes of love, creation, and transformation. The connection is evident in the characterization of the lyrical subject as lonely and misanthropic, but also in relation to the poetic addressee. The beloved is lavished with gifts and attentions, and the lyrical subject wishes to make her bloom. The comparative analysis, besides confirming the presence of a new classical hypotext in Veinte poemas de amor y una canción desesperada, suggests new avenues of interpretation of the collection, especially in the cycle dedicated to Marisombra, whose passivity is akin to Pygmalion’s statue. This contribution can contribute to a better understanding of Neruda’s work and emphasize the relevance of the classical tradition, never sufficiently highlighted, in his poetry.